2004
DOI: 10.1590/s1413-86702004000100004
|View full text |Cite
|
Sign up to set email alerts
|

SENTRY antimicrobial surveillance program report: latin american and brazilian results for 1997 through 2001

Abstract: The alarming emergence and spread of antimicrobial resistance among common bacteria threatens the effectiveness of therapy for many infections. Surveillance of antimicrobial resistance is essential to identify the major problems and guide adequate control measures. Several resistance surveillance programs have been implemented in North America and Europe in the last decade; however, very few programs have assessed antimicrobial resistance in Latin American countries. The SENTRY Antimicrobial Surveillance Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
1
21

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(98 citation statements)
references
References 12 publications
8
63
1
21
Order By: Relevance
“…Regarding tetracycline, although the enterococci resistance rate decreased over time, it remained high in 2009 (57%), but was slightly lower than that reported by the SENTRY Program for Latin America (67.2%) 31 and by other Brazilian studies performed with clinical enterococci strains isolated in 1996 and 1997 (62%) 32 and in 2006 and 2007 (66.5%) 8 . Likewise, the resistance rates to erythromycin were very high, despite the significant decrease observed (95% to 80.6%), confirming that resistance to this drug is very common among enterococci 1,8,31,33 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 57%
See 2 more Smart Citations
“…Regarding tetracycline, although the enterococci resistance rate decreased over time, it remained high in 2009 (57%), but was slightly lower than that reported by the SENTRY Program for Latin America (67.2%) 31 and by other Brazilian studies performed with clinical enterococci strains isolated in 1996 and 1997 (62%) 32 and in 2006 and 2007 (66.5%) 8 . Likewise, the resistance rates to erythromycin were very high, despite the significant decrease observed (95% to 80.6%), confirming that resistance to this drug is very common among enterococci 1,8,31,33 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 57%
“…Likewise, the resistance rates to erythromycin were very high, despite the significant decrease observed (95% to 80.6%), confirming that resistance to this drug is very common among enterococci 1,8,31,33 .…”
Section: Conflict Of Interest Financial Support Referencesmentioning
confidence: 61%
See 1 more Smart Citation
“…Sader et al reported that 80% of SCoN recovered from blood in Latin America were oxacillin resistant [9]. Susceptibility testing by phenotypic methods can be problematic for the detection of methicillin resistance in SCoN because of heterogeneous expression in many strains, affected by growth conditions and by the nature of the beta-lactam agents that are used [10].…”
mentioning
confidence: 99%
“…Several reports of the SENTRY program have been published through more than 10 years of collaboration. In 2004, we reported the in vitro activity of several antimicrobial agents against more than 20,000 clinical isolates collected from different medical centers in Latin America (Sader et al 2004). These data have been used to guide empirical therapy and the local implementation of measures for infection control and prevention.…”
Section: Contributions Of the Special Microbiology Laboratory-unifespmentioning
confidence: 99%